2010
DOI: 10.1590/s1679-45082010ao1208
|View full text |Cite
|
Sign up to set email alerts
|

Nursing and spirituality

Abstract: Objectives: To evaluate the spiritual well-being of nurses; to appraise their opinions as to the importance of offering patients spiritual assistance, and to verify whether nurses received any specific type of preparation during their professional training for giving spiritual assistance to patients. Methods: This is an exploratory and descriptive study, carried out with a sample of 30 nurses who worked at the Stepdown Unit and Oncology Unit of Hospital Israelita Albert Einstein, using the application of the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
7

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 10 publications
1
8
0
7
Order By: Relevance
“…In line with this study, surveys [13][14][15][16][17] published in the literature have found that nurses acknowledge the importance of spirituality in personal and professional spheres; and they find a diagnosis, acknowledge the spiritual needs of patients and/ or of their families, but do not prescribe relevant interventions. Therefore, they do not continue care and leave aside an important aspect of care.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…In line with this study, surveys [13][14][15][16][17] published in the literature have found that nurses acknowledge the importance of spirituality in personal and professional spheres; and they find a diagnosis, acknowledge the spiritual needs of patients and/ or of their families, but do not prescribe relevant interventions. Therefore, they do not continue care and leave aside an important aspect of care.…”
Section: Discussionsupporting
confidence: 68%
“…However, other studies [13][14][15][16][17] showed a low frequency of psycho-emotional diagnoses in patient charts. Charts of patients admitted to an intensive care unit had only three nursing diagnoses related to psychosocial needs and none of them referred to psycho-spiritual needs, which shows that nurses who provide care are still oriented toward a medical-centered model, according to the analysis of records.…”
mentioning
confidence: 94%
“…The inclusion criteria for selection were used: Publications and articles in Portuguese, due to the concept/term extraction tool recognizing only concepts in that language; official article or publication available, free and original, given the fact that the reviews are very extensive and repetitive and highlight ideas present in original studies; published from 2005 to 2016. At the end, four official publications/guidelines [13][14][15][16] and eight scientific articles, [17][18][19][20][21][22][23][24] totaling 12 files to extract the relevant concepts/terms for nursing care directed to people with metabolic syndrome.…”
Section: Methodsmentioning
confidence: 99%
“…Bireyin duygusal stres, fiziksel hastalık ve ölüm gibi değer ve inançlarının tehdit edildiği ya da varoluşsal bir kriz yaşadığı zor zamanlarında ortaya çıkan spiritüel gereksinimlerinin karşılanması, bireyin inanç ve değerleriyle sağlık bakım hizmetleri arasındaki çatış-mayı azaltarak sağlığına olumlu katkı sağlayacaktır (8) . Akıl, beden ve ruh arasında uyumsuzluğun yaşan-dığı kriz zamanlarında, hemşirelerin bireyin kaygıla-rını dinleme, empati yapma gibi spiritüel bakım girişimlerinde bulunmasının hastaların ağrı ve anksiyetesini azalttığı (20,21) , fizyolojik, psikolojik ve mental rahatlığı ve iletişimi artırdığı, iyileşme sürecini olumlu etkilediği belirlenmiştir (9) . Hemşireler bireyin kendini güçlü hissetmesine, hastalıklarla ve getirdiği sorunlarla baş etme stratejileri geliştirmesine ve bu stratejileri uygulamasına destek olarak yaşam kalitesini arttırmasına yardım etmelidirler (7) .…”
Section: Spiritüalizm Ve Hemşirelikunclassified